CD8+ T-cell responses to different HIV proteins have discordant associations with viral load - Kiepiela, Photini; Ngumbela, Kholiswa; Thobakgale, Christina; Ramduth, Dhanwanthia; Honeyborne, Isobella; Moodley, Eshia; Reddy, Shabashini; Pierres, Chantal de; Mncube, Zenele; Mkhwanazi, Nompumelelo; Bishop, Karen; Stok, Mary van der; et al. (Nature Medicine, 2006)
Selection of T-cell vaccine antigens for chronic persistent viral infections has been largely empirical. To define the relationship, at the population level, between the specificity of the cellular immune response and viral control for a relevant human pathogen, we performed a comprehensive analysis of the 160 dominant CD8+ T-cell responses in 578 untreated HIV-infected individuals from KwaZulu-Natal, South Africa. Of the HIV proteins targeted, only Gag-specific responses were associated with lowering viremia. Env-specific and Accessory/Regulatory protein–specific responses were associated with higher viremia. Increasing breadth of Gag-specific responses was associated with decreasing viremia and increasing Env breadth with increasing viremia. Association of the specific CD8+ T-cell response with low viremia was independent of HLA type and unrelated to epitope sequence conservation. These population-based data, suggesting the existence of both effective immune responses and responses lacking demonstrable biological impact in chronic HIV infection, are of relevance to HIV vaccine design and evaluation.